STUDI ETNOMEDISIN MASYARAKAT SUKU LAMPUNG SAIBATIN DI KECAMATAN NGARAS KABUPATEN PESISIR BARAT - Winandari, Ovi Prasetya; Saputri, Dwijowati Asih; Pratiwi, Retno; Anisya, Shinta (FKIP Universitas Tanjungpura, 2024)
Conventional medicine is a course of action that used plants as medication, but there is little understanding of medicinal plants. The purpose of this investigation is to identify the varieties of plants that have therapeutic uses and the parts of plants that the Lampung Saibatin tribal community uses as medicinal plants, identify the methods by which the Lampung Saibatin tribal community uses medicinal plants. Ethnic group known as the Lampung in the Pesisir Barat Regency's Ngaras District. This study intends to identify the kinds of plants that are considered medicinal, ascertain certain plant components are utilized medicinally by the native community of Lampung Saibatin, ascertain the methods by which the Lampung Saibatin tribal community employs medicinal plants, and ascertain the manner. Plants in the Zingibereceae family are utilized by many people and 33 families; in traditional medicine, Fruits, rhizomes, shoots, sap, roots, stems, and leaves are among the plant parts that are used. Grated, chopped, squeezed, ground, soaked, boiled, pounded, torched, and eaten raw are the processing techniques.